Rekonstruksi Pariwisata Bali Pasca Pademi Covid-19 - Ni Nyoman Sri Ratnawati; I.B.Gde Upadana; Putri, A.A Sagung Ayu Srikandi (Jurnal Kajian dan Terapan Pariwisata, 2023)
The Covid-19 pandemic has been in stated since April 13th, 2020 based on Presidential Decree No. 12 of 2020 concerning the Determination of Non-Natural Disasters of Spreading Covid-19 as a National Disaster. After the Covid-19 pandemic which has undermined Bali's economic foundation, namely tourism, the discourse on economic migration is getting stronger. Although this is an old discourse, what must be prepared from now on is human resources and digital infrastructure to move towards economic migration.Today is the right moment for Bali to migrate from the tourism sector to other sectors. In the short term, Bali must be made as a green zone to reactivate tourism and the incentives for the entrepreneurs, either debt restructuring or liquidity assistance is needed, so that the tourism entrepreneurs can back to their productivity. And the need for social assistance to increase people's purchasing power. Meanwhile, in the long terms tourism is no longer a buffer for Bali's economy, in the future the tourism sector will develop in a broad sense and the agricultural product processing industry. Economic migration with the kerthi economic roadmap is in line with the paradigm of sustainable economic development that aims not only to meet the needs of the present but also of future generations. Modern civilization with digitalization must be addressed by the Balinese by changing the mindset so that it creates a portfolio of Balinese income with relatively low risk. Issued of the high uncertainty tourism makes the focus on agriculture in a broad sense, fisheries and the digitization of MSMEs are strategic targets for economic resilience. With the branding owned by Bali, the Balinese people must be ready to enter the new normal era that ensures the safety and comfort of anyone who does business in Bali. Thus, Bali must become the center of gravity in digital business, in addition to existing traditional businesses. Cultural heritage and the adoption of industry 4.0 must be a priority in developing the capacity of the Balinese people. Everything is for the welfare of the Balinese people.